Effects of manipulation of the thorax and intensity of the pressure biofeedback unit on the superficial cervical flexors muscle during craniocervical flexion exercise - Yang, Jin Mo (J Phys Ther Sci, 2017)
[Purpose] This study examined the effects of manipulation of the thorax and the intensity of the pressure biofeedback unit on the superficial cervical flexors muscle during craniocervical flexion exercise. [Subjects and Methods] Thirty three subjects participated in the experiment. Thirty three healthy people without any orthopedic history were also selected. The subjects could monitor the pressure applied to cervical vertebra 3 of the craniocervical junction by markings on the pressure biofeedback unit. Craniocervical flexion exercise was performed for 20 seconds per pressure, and two minutes of rest was allowed after exercise to reduce muscle fatigue. [Results] Significant differences in the post-training gains in the sternocleidomastoid and scalene were observed between the thorax fixation group and thorax non-fixation group. The thorax fixation group showed that muscle activation of the sternocleidomastoid and scalene was increased when the pressure biofeedback unit intensity was 40 mmHg than when pressure biofeedback unit intensity was 20 mmHg and 30 mmHg in the post-hoc result. The thorax non-fixation group showed that muscle activation of the sternocleidomastoid and scalene was higher when the pressure biofeedback unit intensity was 40mmHg compared to that when the pressure biofeedback unit intensity was 20mmHg in the post-hoc result. [Conclusion] Craniocervical flexion exercise is a clinically effective method that reduces the superficial neck flexor muscle activation.